Short‐term reliability evaluation of integrated electricity and gas systems considering dynamics of gas flow. Issue 20 (10th June 2021) - Wang, Sheng; Ding, Yi; Han, Xiaoqing; Wang, Peng; Goel, Lalit; Ma, Jien
Abstract: With the adoption of gas‐fired units (GFU), the interaction between the electricity and gas systems has been intensified. The failure of the gas sources may lead to the insufficiency of the gas supply to the GFUs, and further result in the electricity supply shortage, threatening reliabilities of electricity and gas systems. However, compared with the electric power flow, the dynamics of the gas flow are much slower. Most of the existing studies evaluated the reliabilities of integrated electricity and gas systems (IEGS) without considering the slower dynamics of gas flow, which are not fully accurate in the short‐term. This paper proposes a short‐term reliability evaluation technique for IEGS considering the gas flow dynamics. Firstly, the short‐term reliability models of gas sources, GFUs, and gas compressors are developed. Then, the multi‐stage contingency management scheme is proposed, where gas flow dynamics are analysed for determining the time‐varying load curtailments of electricity and gas. Moreover, a time‐sequential Monte Carlo simulation technique is developed with the finite‐difference scheme to tackle the gas flow dynamics during the short‐term reliability evaluation. Finally, the proposed reliability evaluation technique is validated using an integrated IEEE reliability test system and the practical Belgium gas transmission system.